2010
DOI: 10.1016/j.bpj.2010.06.035
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminus of the Intrinsically Disordered Protein α-Synuclein Triggers Membrane Binding and Helix Folding

Abstract: Alpha-synuclein (aS) is a 140-amino-acid protein that is involved in a number of neurodegenerative diseases. In Parkinson's disease, the protein is typically encountered in intracellular, high-molecular-weight aggregates. Although aS is abundant in the presynaptic terminals of the central nervous system, its physiological function is still unknown. There is strong evidence for the membrane affinity of the protein. One hypothesis is that lipid-induced binding and helix folding may modulate the fusion of synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
237
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(251 citation statements)
references
References 57 publications
12
237
2
Order By: Relevance
“…5B). Our binding results correlate well with data for the folding of AS into ␣-helical form in DPPC systems below the phase transition temperature (37). Evidently, AS has a much greater affinity for neutral membranes in the gel than in the L d phase.…”
Section: As Labeling and Labelsupporting
confidence: 84%
See 1 more Smart Citation
“…5B). Our binding results correlate well with data for the folding of AS into ␣-helical form in DPPC systems below the phase transition temperature (37). Evidently, AS has a much greater affinity for neutral membranes in the gel than in the L d phase.…”
Section: As Labeling and Labelsupporting
confidence: 84%
“…It has been reported that AS interacts preferentially with membranes in the liquid disordered (L d ) phase (29, 34 -36). However, there are instances in which AS demonstrates a higher affinity for rigid and raftlike domains (27,37). Microcalorimetry (isothermal titration calorimetry) indicates that binding of AS to neutral small unilamellar vesicles (SUVs) in the gel phase is stronger than to membranes in the liquid disordered phase (31).…”
mentioning
confidence: 99%
“…It is clear that N-terminal acetylation enhances the helicity of aSyn at its N terminus, and because membrane-bound aSyn becomes highly helical, it is reasonable that N-terminal acetylation would increase the affinity of the protein for membranes. Indeed, we and others have proposed previously that helicity at the N terminus of synuclein is likely a key mediator of early lipid interactions (35,73). On the other hand, N-terminal acetylation eliminates the primary amine group of aSyn and thereby decreases the positive charge of its N-terminal lipid binding domain by 1 at physiological pH.…”
Section: Discussionmentioning
confidence: 84%
“…We and others have shown that the primary consequence of N-terminal acetylation in the free state of aSyn is to increase the helicity of the N-terminal ϳ10 residues (30,32,33), an effect that likely results from the known ability of an N-acetyl group to act as a helix cap (71,72), which would stabilize the transiently helical structure formed at the N terminus. We (35,39) and others (33,73) have postulated that transient helical character at the very N-terminal region may be important in a The population of all bound states was calculated as the ratio of the average intensity ratio of residues 3-9, which are expected to be bound in both fully and partly helical binding modes, to the average intensity ratio of residues 129 -137, which remain unbound even at high lipid concentrations, subtracted from 1. b The population of the extended helix state was calculated as the ratio of the average intensity ratio of residues 65-80, which are in the second half of the lipid binding domain and have well resolved HSQC peaks, to the average intensity ratio of residues 129 -137, subtracted from 1. c Apparent dissociation constants were derived from fitting the bound populations of each state at several lipid concentrations to Equation 2, derived from a simple bimolecular binding equilibrium. See "Experimental Procedures" for a further description.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, on SUVs, multiple ␣S-binding modes (i.e. structural inhomogeneity) exist (30), in accordance with an inhomogeneous sequence distribution of surfactant affinities (29,31). Thus, although an elongated helix will dominate vesicle-bound ␣S, it is unclear to what extent broken helix conformations are populated on SUVs resembling synaptic vesicles.…”
mentioning
confidence: 99%